Faculty and learner’s perception on Benefits and Challenges of Integrated Modular Biochemistry Curriculum - Aftab, Lubna; Faisal, Nabeela; Jan, Fauzia; Usman, Humera; Hakim, Farzana; Abid, Abdul Rahman (Journal of Neonatal Surgery, 2025)
Objective: The objective of this study was to assess the perceptions of students and faculty regarding the transition from a traditional to an integrated medical curriculum, with a particular emphasis on its impact on the teaching and learning of biochemistry. Study design: Cross sectional study Settings: Department of Biochemistry, University Medical & Dental College Faisalabad Duration: From15th January, 2025 to 15th March, 2025 Methods: Ethical approval was obtained from the review committee of The University of Faisalabad. The study included 300 first- and second-year female MBBS students and 52 biochemistry faculty members. Sample size was calculated using the WHO calculator, and participants were selected through simple random sampling. Informed consent was taken, and data was collected via a validated questionnaire (Google Forms) and analyzed using descriptive statistics in SPSS Results: Both students and teachers reported overall positive perceptions of the integrated biochemistry curriculum, with the strongest agreement on its role in connecting basic and clinical sciences. OSVE was viewed favorably as an assessment tool, while students were more satisfied with integrated assessments than teachers. Key challenges included content overload and difficulty in achieving subject integration. All findings were statistically significant (p < 0.05). Most students agreed that integrated biochemistry improved concept retention, aligned practicals with theory, and supported peer interaction, though many reported insufficient time for revision and increased cognitive load. Conclusion: The integrated biochemistry curriculum was generally perceived positively by both students and faculty, especially for strengthening the connection between basic and clinical sciences and enhancing research and communication skills. Nevertheless, challenges related to content overload, cognitive burden, and limited revision time highlight the need for refinement. Future curriculum planning should address these issues to maximize the benefits of integration